Analysis of Upstream Regulators, Networks, and Pathways Associated With the Expression Patterns of Polycystic Ovary Syndrome Candidate Genes During Fetal Ovary Development - Azumah, Rafiatu; Hummitzsch, Katja; Hartanti, Monica D.; St. John, Justin C.; Anderson, Richard A.; Rodgers, Raymond J. (Frontiers in Genetics, 2022)
Polycystic Ovary Syndrome (PCOS) is a multifactorial syndrome with reproductive, endocrine and metabolic symptoms, affecting about 10% women of reproductive age. Pathogenesis of the syndrome is poorly understood with genetic and fetal origins being the focus of the conundrum. Genetic predisposition of PCOS has been confirmed by candidate gene studies and Genome-Wide Association Studies (GWAS). Recently, the expression of PCOS candidate genes across gestation has been studied in human and bovine fetal ovaries. The current study sought to identify potential upstream regulators and mechanisms associated with PCOS candidate genes. Using RNA sequencing data of bovine fetal ovaries (62-276 days, n = 19), expression of PCOS candidate genes across gestation was analysed using Partek Flow. A supervised heatmap of the expression data of all 24,889 genes across gestation was generated. Most of the PCOS genes fell into one of four clusters according to their expression patterns. Some genes correlated negatively (early genes; C8H9orf3, TOX3, FBN3, GATA4, HMGA2 and DENND1A) and others positively (late genes; FDFT1, LHCGR, AMH, FSHR, ZBTB16 and PLGRKT) with gestational age. Pathways associated with all the genes in each cluster were determined using Ingenuity Pathway Analysis software (IPA), KEGG pathway analysis and Gene Ontology (GO) databases using DAVID bioinformatics. Genes in the early gene group were involved in mitochondrial function, the upstream regulators included PTEN, ESRRG/A and MYC and oxidative phosphorylation and mitochondrial dysfunction pathways were the top canonical pathways. Genes in the late group were involved in stromal expansion, cholesterol biosynthesis and steroidogenesis and upstream regulators included TGFB1/2/3, TNF, ERBB2/3, VEGF, INSIG1, POR and IL25. These findings provide insight into ovarian development of relevance to the origins of PCOS, and suggest that multiple aetiological pathways might exist for the development of PCOS.